Review of Drug Quality and Security Act of 2013: The Drug Supply Chain Security Act (DSCSA) - Elona Gjini; Albert I Wertheimer (University of Minnesota Libraries Publishing, 2016)
The Drug Supply Chain Security Act (DSCSA) signed into law in November 27, 2013 by president Obama creates a uniform national standard for tracing drug products through the supply chain. The goal of DQSA is to enhance FDA's ability to help protect consumers by detecting and removing potential dangerous products from the pharmaceutics distribution supply chain. A new electronic, interoperable system will identify and trace only prescription drugs in the finished form for human use while distributed in the United States. The purpose of this review was to shed light on a complex and complicated process that it will require cooperation between FDA and drug manufactures, wholesale drug distributors, repackagers and dispensers. The implementation of the DSCSA is based on several law requirements and FDA has developed a schedule with time frames for each of them to be executed over a 10-year period. From this review, FDA recommendations are provided through the FDA Guidance on Identifying Suspect Product document to help trading partners and provide information about the risk of suspect drugs entering the supply chain. Moreover, FDA organized on April 5-6, 2016 in Silver Spring, MD a public workshop to gather valuable feedback from stakeholders who shared their input about the implementation of the new electronic system and its requirements. By the end of 2023, a unified system will provide easier data exchange and less errors, and will increase the safety and security of the pharmaceutical distribution supply chain.   Type: Student Project